Role of Antimicrobial Peptides in Periodontal Health and Disease—A Review - Ruchita T Patil; Prasad V. Dhadse; Anand N. Wankhede; Sanehi D. Punse (Journal of Pharmacy and Bioallied Sciences)
Periodontitis is an inflammatory condition that results from the interaction between the host immune system and periopathogens, which leads to the development of periodontal attachment loss, periodontal pocket, and resorption of the alveolar bone. With advances in scientific research on antimicrobial peptides (AMPs), they play a crucial role in modulating immune response as well as act as antimicrobials. This review is focused on the role of AMPs in maintaining the periodontal health.